Effect of resilient joints on the airborne sound insulation of single-leaf heavyweight constructions. (15th September 2022) - Keränen, Jukka; Hongisto, Valtteri
Abstract: The joint between a heavyweight construction and the surrounding building frame can be rigid or resilient. It is often believed that a resilient joint improves sound insulation. The purpose of this study was to investigate how the joint resiliency of a single-leaf heavyweight construction affects the sound reduction index and the total loss factor. A masonry wall of 10 m 2 (220 kg/m 2 calcium silicate block wall) was built three times (A−C) in laboratory using three different joint types between the wall perimeter and the test opening frame: A - All four joints rigid; B - Three joints resilient and one rigid; C - All four joints resilient. The sound reduction index was determined using both pressure and intensity method. The total loss factor was determined by measuring the structural reverberation time using hammer impacts. The sound reduction index reduced significantly with increasing level of resiliency. For joint type A, the weighted sound reduction index, R w, was 50 dB while it was 45 dB for B and 43 dB for C. Correspondingly, the total loss factor reduced from A to C, i.e., with increasing joint resiliency. The effect of joint type was evident above the coincidence frequency (250 Hz) of the block wall. Resilient joint prevented the energy transmission from the wall to the building frame, which increased the sound radiation to the air, which was reflected as reduced sound reduction index. The results imply that the joints of a heavyweight construction shall be rigid if high sound reduction index is desired above the coincidence frequency. On the other hand, the increased joint resiliency improved the sound reduction index at most frequency bands below the coincidence frequency. Resilient joints around heavyweight construction can be beneficial in situations where the reduction of low-frequency noise is of primary concern. Highlights: Sound insulation of a masonry wall was tested with three joint types. The joint types were rigid, partially resilient, and fully resilient. The worst sound insulation was obtained with fully resilient condition. At low frequencies, the resilient joint improved sound insulation. Rigid joints should be used if high sound insulation is desired.